A filiação socioafetiva e o Supremo Tribunal Federal - Motta, Allana Roberta Vianna (2021)
This study has as its research object the institute of socio-affective affiliation from the perspective of the Supreme Federal Court, taking into account the constitutional and legal dictates, the principles applicable to Family Law, as well as the teachings found in Brazilian doctrine. To delimit this study, we pose the following problem: does the STF have limitations to the recognition of socio-affective affiliation? If so, which ones? To answer these questions, we point out the links and criteria established by the Supreme Court for this recognition, in order to guarantee legal security for family relationships not yet provided for in the legislation. For this purpose, the systematic logical method is used, the Federal Constitution being the first reference and, based on selective, critical, reflective and analytical readings of ordinary legislation and doctrine, demonstrate the social scope of the norm. In addition, a jurisprudential analysis of specific cases on the subject was carried out, in order to verify the content of the judgments in Brazilian courts. Still in order to contextualize the work, we discuss what is the socio-affective affiliation, what are the requirements and parameters listed by the doctrine and explain the principles that serve as the basis for its recognition. Thus, based on civil-constitutional hermeneutics, the Supreme Federal Court endorses the recognition of socio-affective affiliation and multiparenting as a new paradigm for family constitution